Follicular conjunctivitis caused by Chlamydia trachomatis in an infant Saharan population: molecular and clinical diagnosis. Issue 2 (1st February 2003) - Javaloy, J; Ferrer, C; Vidal, M T; Alió, J L
Abstract : Aims: To ascertain the prevalence of acute trachoma as a supposed endemic disease among infants in the Saharan refugee camps of Tindouf (Algeria) and to evaluate the efficacy of treatment with a single dose of azithromycin. Methods: 527 children aged between 3 and 17 were evaluated in the camp schools in October 2001. All the children were clinically and microbiologically examined, including slit lamp checks of anterior segment and two conjunctival swabs, one for the detection of membrane lipopolysaccharide by quick immunoassay test Clearview Chlamydia MF and the other for the detection of specific DNA by chlamydia plasmid specific polymerase chain reaction (PCR) assay. After examination, a single dose of azithromycin was administered to each child. One month later samples from positive children and 12 random negative children by the first PCR were taken to perform a new PCR assay. Results: Chlamydia trachomatis was suspected in 2.47% of the children, papillary hypertrophy being the most frequently seen clinical sign. Scarring changes secondary to trachoma were detected in 11.7% of the children. Only four cases (0.8%) were positive to the immunoassay test and 12 cases (2.27%) were positive by PCR. After treatment a second PCR was performed on positive children and they were negative of chlamydia DNA amplification. However, one child who was negative and received the treatment was positive in the second PCR assay. Conclusion: Acute trachoma prevalence is much lower than expected among infants in this Saharan population. The possible reasons could be the recent improvements in hygiene and health care. Cicatricial trachoma is more frequent. The Clearview immunoassay test has very low sensitivity in the detection of this disease. A single dose of azithromycin is sufficient to treat chlamydial conjunctivitis. However, a programme of improvement in hygiene and health care is necessary to prevent re-infection.